How much does mental health discrimination cost: valuing experienced discrimination in relation to healthcare care costs and community participation. (6th June 2014) - Evans-Lacko, S.; Clement, S.; Corker, E.; Brohan, E.; Dockery, L.; Farrelly, S.; Hamilton, S.; Pinfold, V.; Rose, D.; Henderson, C.; Thornicroft, G.; McCrone, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Aims. This study builds on existing research on the prevalence and consequences of mental illness discrimination by investigating and quantifying the relationships between experienced discrimination and costs of healthcare and leisure activities/social participation among secondary mental health service users in England. Methods. We use data from the Mental Illness-Related Investigations on Discrimination (MIRIAD) study (n = 202) and a subsample of the Viewpoint study (n = 190). We examine experiences of discrimination due to mental illness in the domains of personal relationships, community activities, and health care, and how such experienced discrimination relates to patterns of service use and engagement in leisure activities. Results. Our findings show that the cost of health services used for individuals who reported previous experiences of discrimination in a healthcare setting was almost twice as high as for those who did not report any discrimination during the last 12 months (Relative Risk: 1.73; 95% Confidence Interval (CI): 1.39, 2.17) and this was maintained after controlling for symptoms and functioning. Experienced discrimination in healthcare (Relative Risk: 0.83; 95% CI: 0.81, 0.84) or in relationships (Relative Risk: 0.89; 95% CI: 0.87, 0.91), however, was associated with lower participation in, and hence lower costs of, leisure activities. Individuals who reported any discrimination in a healthcare setting had, on average, £434 higher costs associated with health service use while reported discrimination in the community was associated with increased leisure costs of £32. Conclusions. These findings make an important initial step towards understanding the magnitude of the costs of mental health-related discrimination.